Application of indica-japonica single-nucleotide polymorphism markers for diversity analysis of Oryza AA genome species - Lee, Yoo-Jin; Thomson, Michael J.; Chin, Joong Hyoun (Cambridge University Press, 2014)
High-throughput genotyping using single-nucleotide polymorphisms (SNP) is one tool that can be used to study the genetic relationships between wild rice relatives and cultivated rice. In this study, a set of 96 indica–japonica SNP markers, which can differentiate indica and japonica subspecies of rice, were used to characterize 227 Oryza accessions including 93 AA genome accessions from seven wild Oryza species. A total of 72 markers of the 96 markers were selected for the phylogenetic study and allele polymorphism survey. A subset of SNP markers were present only in Oryza sativa and evolutionarily close species, Oryza nivara and Oryza rufipogon. These markers can be used for distinguishing cultivated rice from the other species and vice versa. Eight clusters were generated through phylogenetic analysis, and Oryza meridionalis and Oryza longistaminata appeared to be the most distantly related species to cultivated rice. In this study, Oryza barthii and Oryza glaberrima accessions were found to exhibit high genetic similarity. Across the wild species, more indica-type alleles were detected for most accessions. In this study, a set of markers selected to be informative across O. sativa accessions were used, but it will be interesting to compare the results of this study with SNP data obtained through next-generation sequencing in the future.